(E)-4-Hydroxy-N′-(3-hydroxy-4-methoxybenzylidene)benzohydrazide - Fun, Hoong-Kun (International Union of Crystallography, 2011)
The molecule of the title benzohydrazide derivative, C(15)H(14)N(2)O(4), exists in a trans conformation with respect to the C=N double bond and is twisted, the dihedral angle between the two benzene rings being 24.17 (6)°. The methoxy group is almost co-planar with respect to the attached benzene ring [C(m)—O—C—C (m = methyl) = −1.45 (17)°]. In the crystal, the molecules are linked by N—H⋯O and O—H⋯O hydrogen bonds into sheets parallel to the bc plane. These sheets are further connected into a three-dimensional network by weak C—H⋯O and C—H⋯π interactions.